Routledge History of Loneliness - Barclay, Katie; Chalus, Elaine; Simonton, Deborah (Taylor & Francis, 2023)
The Routledge History of Loneliness takes a multidisciplinary approach to the history of a modern emotion, exploring its form and development across cultures from the seventeenth century to the present. Bringing together thirty scholars from various disciplines, including history, anthropology, philosophy, literature and art history, the volume considers how loneliness was represented in art and literature, conceptualised by philosophers and writers and described by people in their personal narratives. It considers loneliness as a feeling so often defined in contrast to sociability and affective connections, particularly attending to loneliness in relation to the family, household and community. Acknowledging that loneliness is a relatively novel term in English, the book explores its precedents in ideas about solitude, melancholy and nostalgia, as well as how it might be considered in cross-cultural perspectives. With wide appeal to students and researchers in a variety of subjects, including the history of emotions, social sciences and literature, this volume brings a critical historical perspective to an emotion with contemporary significance.